Repetición léxica como abandono y repetición léxica como recurso estilístico (Minerva, 2019)
This paper deals with two kinds of lexical recurrence as carelessness (likely because of remains of the early latin syntax) and as stylistic device, attending both to Caesar's and Vergil's texts respectively.